Nonalcoholic Fatty Liver Disease in University Rugby Football Players - Nirengi, Shinsuke; Fujibayashi, Mami; Furuno, Sachiko; Uchibe, Akihiko; Kawase, Yasuharu; Sukino, Shin; Kawaguchi, Yaeko; Minato, Satomi; Kotani, Kazuhiko; Sakane, Naoki (Frontiers in Endocrinology, 2018)
Physical activity improves various metabolic disturbances. The effect of physical activity on non-alcoholic fatty liver disease (NAFLD) has not been defined, particularly in athletes who are able to consume a diet to increase body mass. The aim of this study was to evaluate the prevalence of NAFLD and associated factors of NAFLD among male university rugby football players (n = 69, 37 forwards [FW] and 32 backs [BK]), relative to age-matched controls (CON; n = 29). For FW players exercise consists of physical contact play, such as ruck, mall, scrum, and tackle. For BK players exercise consists of sprints and endurance running. Liver function tests and bioimpedance analysis to assess body composition were performed. Subjects consuming ≤ 20 g/day of ethanol and exhibiting an aspartate transaminase (AST) level ≥ 33 U/L, and/or alanine transaminase (ALT) level ≥ 43 U/L, were considered to have NAFLD. The PNPLA3 and MTP genotypes were determined using real-time polymerase chain reaction (PCR). The body mass index, body fat mass, and lean body mass were significantly higher in the FW group than in the BK and CON groups (P < 0.05). The total cholesterol, low-density lipoprotein cholesterol, triglyceride, AST, ALT, and alkaline phosphatase levels were significantly higher in the FW group than in the CON group (P < 0.05). The prevalence of NAFLD was significantly higher in the FW group than in the BK group and CON group (18.9%, 8.6%, and 0.0%, respectively), whereas there were non-significant between-group differences in the frequency of the PNPLA3 and MTP genotypes. These findings indicate that rugby football players, especially those in the FW position, are at higher risk of developing NAFLD, which emphasizes the role of diet and exercise in the development of NAFLD.